2020
DOI: 10.3390/ma13225257
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on the Cutting of Metal Materials by Electrical Discharge Machining with Contact Breaking with Metal Band as Transfer Object

Abstract: The scientific paper presents practical research carried out by a mixed team of Romanian researchers from universities and the business environment. The research consists in applying the process of cutting metallic materials through electrical discharge machining with contact breaking using a metal band as a transfer object. The research was implemented with the help of a specially designed installation in the laboratory and subsequently all the necessary steps were taken to obtain the patent for it. Various m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The additional material is censored through a sequence of sparks among the tool and the workpiece in the form of a dielectric medium that works as an insulator to avoid the material declaration reserved externally to the device. The EDM procedure has found numerous uses such as fabrication of molds/dies and the cutting of holes in a variety of materials containing metals and composites [2] by vast distance to diameter ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The additional material is censored through a sequence of sparks among the tool and the workpiece in the form of a dielectric medium that works as an insulator to avoid the material declaration reserved externally to the device. The EDM procedure has found numerous uses such as fabrication of molds/dies and the cutting of holes in a variety of materials containing metals and composites [2] by vast distance to diameter ratio.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Titu et al [15] concluded that there is an economic advantage obtained when cutting semi-finished products of alloy steels by EDMCB, using the metal band as TO (tool).…”
mentioning
confidence: 99%